STUDI PERILAKU CAMPURAN LATASTON (HRS-WC) DENGAN “LIMBAH KARET BAN LUAR” SEBAGAI BAHAN PENGGANTI SEBAGIAN ASPAL - Candra Putra Kiswara; Andi Saiful Amal (Media Teknik Sipil, 2014)
STUDI PERILAKU CAMPURAN LATASTON (HRS-WC) DENGAN“LIMBAH KARET BAN LUAR” SEBAGAI BAHAN PENGGANTISEBAGIAN ASPALCandra Putra Kiswara 1& Andi Saiful A21&2Jurusan Teknik Sipil Fakultas Teknik Universitas Muhammadiyah MalangAlamat korespondensi : Jalan Raya Tlogomas 246 Malang 65144e-mail: candra_sum@yahoo.co.id, andiamal99@yahoo.co.idABSTRACTWaste to be one of the problems facing the nation at this time. Community is very disturbed bythe presence of various types of waste that is around their neighborhood. Ranging from industrialwaste to the waste home.The basic requirements of a road construction is to prepare the surface layer of a flat andstrong to ensure high security for a long time and the preservation of every detail in a variety ofweather. It required an asphalt mixture that is capable of supporting loads as well as capture thedamaging effects of traffic and the weather (climate) and can provide good service.With the addition of waste tire rubber is significantly affect mixture properties such Lataston(HRS-WC) Stability, Marshall Quontient, Flow and Air Voids. This is evidenced by the results oftesting using a Marshall. The average value of stability the average of 1220 kg. For Lataston (HRSWC)mix with additives outer tire rubber to rubber optimum levels (KKO) 11,50%, to produce amixture of qualities: Marshall Stability value = 1220 kg, Marshall Quotient value = 7,2 kN / mm,Value Air Marshall voids = 10,00%, Value Bitumen film thickness = 5,6 mm.Key Word: Waste Tire Rubber, Marshall Caracteristic